Savvy - Law, Ingrid, 1970- (Dial Books for Young Readers ; Walton Media, 2008)
Recounts the adventures of Mibs Beaumont, whose thirteenth birthday has revealed her "savvy"--a magical power unique to each member of her family--just as her father is injured in a terrible accident.